Collaborative Governance through Deep Digital Transformation Creating " Trust" in the Investment and Services Department One Stop Integrated Service (DPMPTSP) Badung Regency - Kadek Wiwin Dwi Wismayanti; Putu Eka Purnamaningsih (International Journal of Educational Research Excellence (IJERE), 2023)
Excellent public service is the goal of providing services to the community. In public services there is an aspect of serving and being served, where the government is the one who serves and the community acts as the one who is served. The community as the party served has a role to participate in improving the quality of public services to make them more responsive. "TRUST" is a form of collaborative governance organized by the Badung Regency Investment and Integrated Services Service (DPMPTSP) and this collaboration is carried out with the community. "TRUST" is a measurement of integrity carried out in the form of an integrity service survey. This research aims to find out how collaborative governance in the Department of Investment and One Stop Integrated Services is in realizing services based on "TRUST" (Transparency, Responsibility, Upright, Sustainable, Technology). This research uses descriptive qualitative methods. The research object in this study is at the Badung Regency Investment and One Stop Integrated Services Service. Data collection techniques were carried out by means of interviews, literature study, documentation and observation. The research informant is the Sub-Coordinator for Reporting and Evaluation of the Badung Regency Investment and One-Stop Integrated Services Service and the community who receives services at the Badung Regency DPMPTSP. The results obtained show that collaborative governance is working well in realizing trust, supported by the results of the integrity assessment which shows very high integrity. In providing trust-based services, Badung Regency DPMPTSP has fulfilled every indicator.